Diallyl Trisulfide Prevents Adipogenesis and Lipogenesis by Regulating the Transcriptional Activation Function of KLF15 on PPARγ to Ameliorate Obesity. Issue 22 (2nd September 2022) - Hu, Yanzhou; Xu, Jia; Gao, Ruxin; Xu, Ye; Huangfu, Bingxin; Asakiya, Charles; Huang, Xianghui; Zhang, Feng; Huang, Kunlun; He, Xiaoyun; Luo, Yunbo
Abstract : Scope: Diallyl trisulfide (DATS) is a bioactive compound in garlic. The anti‐obesity effect of garlic oil has been reported, but the role and mechanism of DATS in preventing obesity remain to be explored. Methods and results: Studies with high‐fat‐diet‐induced obese mice and 3T3‐L1 adipocytes are performed. The results show that DATS significantly reduces lipid accumulation and repairs disordered metabolism in vivo by restraining adipogenesis and lipogenesis, and promoting lipolysis and fatty acid oxidation in white adipose tissue. In cells, DATS plays different roles at different stages of adipocyte differentiation. Notably, DATS reduces lipid accumulation mainly by inhibiting adipogenesis and lipogenesis at the late stage. KLF15 is knocked down in 3T3‐L1 cells, which eliminate the inhibitory effect of DATS on adipogenesis and lipogenesis. The dual‐luciferase reporter and ChIP assays indicate that DATS can inhibit the transcriptional activation function of KLF15 on PPARγ by inhibiting the binding of KLF15 to PPARγ promoter. The function comparison of structural analogs and the intervention of dithiothreitol show that disulfide bond is crucial for DATS to work. Conclusion: DATS prevents obesity by regulating the transcriptional activation function of KLF15 on PPARγ. Abstract : Diallyl trisulfide reduces lipid accumulation to prevent diet‐induced obesity by inhibiting the binding of KLF15 to PPARγ promoter at the late stage of adipocyte differentiation.